Cognitive analysis of schizophrenia risk genes that function as epigenetic regulators of gene expression. Issue 8 (20th October 2016) - Whitton, Laura; Cosgrove, Donna; Clarkson, Christopher; Harold, Denise; Kendall, Kimberley; Richards, Alex; Mantripragada, Kiran; Owen, Michael J.; O'Donovan, Michael C.; Walters, James; Hartmann, Annette; Konte, Betina; et al.
Abstract : Epigenetic mechanisms are an important heritable and dynamic means of regulating various genomic functions, including gene expression, to orchestrate brain development, adult neurogenesis, and synaptic plasticity. These processes when perturbed are thought to contribute to schizophrenia pathophysiology. A core feature of schizophrenia is cognitive dysfunction. For genetic disorders where cognitive impairment is more severe such as intellectual disability, there are a disproportionally high number of genes involved in the epigenetic regulation of gene transcription. Evidence now supports some shared genetic aetiology between schizophrenia and intellectual disability. GWAS have identified 108 chromosomal regions associated with schizophrenia risk that span 350 genes. This study identified genes mapping to those loci that have epigenetic functions, and tested the risk alleles defining those loci for association with cognitive deficits. We developed a list of 350 genes with epigenetic functions and cross‐referenced this with the GWAS loci. This identified eight candidate genes: BCL11B, CHD7, EP300, EPC2, GATAD2A, KDM3B, RERE, SATB2 . Using a dataset of Irish psychosis cases and controls (n = 1235), the schizophrenia risk SNPs at these loci were tested for effects on IQ, working memory, episodic memory, and attention. Strongest associations were for rs6984242 with both measures of IQ ( P = 0.001) and episodic memory ( P = 0.007). We link rs6984242 to CHD7 via a long range eQTL. These associations were not replicated in independent samples. Our study highlights that a number of genes mapping to risk loci for schizophrenia may function as epigenetic regulators of gene expression but further studies are required to establish a role for these genes in cognition. © 2016 Wiley Periodicals, Inc.